Talk About a Racial Eclipse: Narratives of Institutional Evasion in an Urban School–University Partnership. (March 2017) - Phelps Moultrie, Jada; Magee, Paula A.; Paredes Scribner, Samantha M.
During a student teaching experience, teacher education candidates affiliated with an urban School of Education school–university partnership witnessed a disturbing interaction between an early career White male teacher and a first-grade Black male student at an assigned elementary school. The subsequent interactions among the teacher, principal, district administrators, and university partners illumine the racial implications at varying levels from the individual to the structural level. The ways in which race is centered, yet is evaded by school actors, raises important considerations for leadership. Authors suggest combining critical race theory with organizational narratives to explore the dilemmas at various structural levels, but in particular for the principal and district-level administrators.